Vehicle handling dynamics : theory and application - Abe, Masato (Butterworth-Heinemann, 2015)
Vehicle dynamics are vital for optimizing a vehicle's drivability, efficiency, and safety. Understanding the forces and motions on a vehicle (both theoretical aspects, like basic equations of motion, and practical ones, like tire mechanics and human vehicle control) is integral in the design and development of all vehicles. Masato Abe's Vehicle Handling Dynamics, Second Edition, provides comprehensive coverage of vehicle dynamics, enabling readers to visualize and invent better vehicles. Vehicle Handling Dynamics begins with an overview of the fundamental theories of vehicle handling dynamics, based on simple equations of motion. The book then extends to driver-vehicle behavior, handling quality and active vehicle motion control. In addition, this new edition includes two new chapters. Chapter 9 covers vehicle motion control for electric vehicles, crucial in this new era of automobiles. Chapter 12 studies the classic issue of model-based handling quality evaluations (challenging the traditional dependencies on test drivers for determining a vehicle's drivability). Written by one of the most distinguished authorities in the area, Vehicle Handling Dynamics, Second Edition, lends equal and careful consideration to both theory and application, providing valuable insights for students of and engineers working in vehicle dynamics and control.